DECONSTRUCTION OF CHINA’S ANTHROPOCENTRIC VIEWS IN JIANG RONG’S WOLF TOTEM NOVEL - Woro Januarti (Faculty of Languages and Arts, Universitas Negeri Yogyakarta, 2020)
The Industrial Revolution in the mid-nineteenth century had transformed the relationship between man and nature into one that was confused: man and nature were either balanced or mutually antagonistic. In China itself, since the “Great Leap Forward Movement,” “Cultural Revolution,” “Deng Xiaoping’s Open Politics” to date, has caused severe damage to nature. These have caused various kinds of public reactions, both from the public, academia, society, and writers. Deconstruction Wolf Totem anthropocentric view from an ecological perspective can show China’s culture, environmental conditions, government policies, the relation of human and natural, ecofeminism, eco-spiritualism, and anti-ecological thought. The method used in this study is descriptive interpretive in ecocritical studies. Ecocritical perspective on literary works is essential means to speaking out against anthropocentric domination and environmental damage. The analysis results show that the ecological damage narrative in Wolf Totem is used as a reinforcing motive to deconstruct the anthropocentric view of the people of China and Chinese government policy. Through the deconstruction of an anthropocentric perspective, efforts to repair environmental damage carried out. By changing the anthropocentric culture to become ecocentric, will achieve a green China, especially in the Xi Jinping era whose policies oriented towards Ecological Civilization (生态文明). Keywords: ecocritic, Chinese ecological literature, ecofeminism, eco-spiritualism, anti-ecology DEKONSTRUKSI PANDANGAN ANTROPOSENTERIK CHINA DALAM NOVEL WOLF TOTEM KARYA JIANG RONGSAbstrakRevolusi Industri pada pertengahan abad sembilanbelas telah merubah hubungan manusia dengan alam menjadi sebuah hubungan yang membingungkan: manusia dan alam menjadi baik dan seimbang atau saling bermusuhan. Di Tiongkok sendiri, sejak “Gerakan Lompatan Jauh ke Depan